Toxicogenomic activity of gemcitabine in two TP53-mutated bladder cancer cell lines: special focus on cell cycle-related genes - Silva, Glenda Nicioli da [UNESP]; Camargo, Elaine Aparecida de [UNESP]; Salvadori, Daisy Maria Favero [UNESP] (Springer, 2012)
Because of its lower toxicity and good tolerability and response, gemcitabine has been described as one of the most highly promising drugs for urinary bladder cancer therapy. Its phosphorylated active-dFdCTP metabolite can incorporate into DNA, causing replication blockage. Additionally, it is known that mutations in the TP53 gene are related to the high recurrence rate of these neoplasias. Based on these premises, we investigated the effects of gemcitabine on the expression of the cell cycle-related genes in two different TP53-mutated bladder transitional carcinoma cell lines-5637 (from a moderate-grade tumor with a TP53 allele carrying two mutations) and T24 (from an invasive tumor with a TP53 allele encoding an in-frame deletion). Cell viability and morphology analyses (phase-contrast photomicrographs), Nuclear Division Index and pathway-specific quantitative RT-PCR gene arrays were performed. Treatment with gemcitabine led to the following results: (1) a significant decrease of viable T24 cells after treatment at the highest concentration (3.12 mu M) tested; (2) scattered, elongated and vacuolated 5637 and T24 cells; (3) a cytostatic effect in both cell lines; and (4) significant upregulation of the BRCA1, CCNE1, CDK2, CDK6, CDKN1A, CDKN2B, E2F4, GADD45A, MAD2L2, CCNH, SERTAD1, CDC1, and CHEK1 genes. Gemcitabine had distinct toxicogenomic effects in the bladder transitional carcinoma cell lines with two different TP53 mutations. However, independent of the type of mutation and tumor grade, gemcitabine induced cell cycle arrest; upregulation of DNA repair-related genes, G1/S transition, apoptosis and activation of transcription factors, mainly by upregulation of the CCNE1, CDKN1A and GADD45A genes.
Keywords: Chemotherapy; Gemcitabine; Gene expression profiling; Mutated TP53 cell lines